2014
DOI: 10.1016/j.asjsur.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Maggot therapy for chronic ulcer: A retrospective cohort and a meta-analysis

Abstract: Our evidence suggests that MWT is significantly better for wound healing and more cost-effective than CWT. An updated meta-analysis or large scale randomized controlled trial (RCT) is required to confirm this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 26 publications
2
39
0
2
Order By: Relevance
“…The use of larval therapy to enhance wound healing remains unsupported with only five studies identified, each of which had a high risk of bias …”
Section: Recommendationsmentioning
confidence: 99%
“…The use of larval therapy to enhance wound healing remains unsupported with only five studies identified, each of which had a high risk of bias …”
Section: Recommendationsmentioning
confidence: 99%
“…There is no doubt maggots debride infected and necrotic wounds, but formal investigation of their influence on wound healing has been limited. Recent publications, including a randomized controlled trial and meta‐analysis, have demonstrated a reduction in healing time and the effective removal of necrotic tissue …”
Section: Introductionmentioning
confidence: 99%
“…Wilasrusmee et al found MDT helpful in the treatment of chronic ulcers with a 20% greater chance of wound healing as compared to conventional therapies. 60 Tian et al (2013) reviewed the efficacy of MDT compared with standard of care for diabetic foot ulcers. 61 Four studies (356 participants) were meta-analyzed with the conclusion that the evidence for MDT was too weak to routinely recommend it for treatment.…”
Section: Meta-analyses Of Mdt Studiesmentioning
confidence: 99%